X=36/4x=97x+3x+10-8=6(x+3)

Simple and best practice solution for X=36/4x=97x+3x+10-8=6(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X=36/4x=97x+3x+10-8=6(x+3) equation:



X=36/4X=97X+3X+10-8=6(X+3)
We move all terms to the left:
X-(36/4X)=0
Domain of the equation: 4X)!=0
X!=0/1
X!=0
X∈R
We add all the numbers together, and all the variables
X-(+36/4X)=0
We get rid of parentheses
X-36/4X=0
We multiply all the terms by the denominator
X*4X-36=0
Wy multiply elements
4X^2-36=0
a = 4; b = 0; c = -36;
Δ = b2-4ac
Δ = 02-4·4·(-36)
Δ = 576
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{576}=24$
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-24}{2*4}=\frac{-24}{8} =-3 $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+24}{2*4}=\frac{24}{8} =3 $

See similar equations:

| 40=-3d+7 | | 30=5(2x-1) | | 72=2x+6(1-4x) | | 3(x–2)–(x+5)=17 | | 6m-3-2m=5 | | 4b-10=3(b+2) | | 7a+11=67 | | X+17+x+2=83 | | 3.5+10m=7.92 | | 87=2x+15+4x+6 | | x=43x+17 | | 3.1+10m=8.96 | | 2w-2/5=8/5 | | −5(−2x−1)-5x+2=27 | | m/3+14=33;9 | | 5y=95= | | 3.1=c-1.5 | | 17y-7=19y+7 | | 11m=650+88m | | 1/4x-2+3x=3/2x+3+3/2x | | 1.5p=8+1.25p | | 6y+8y=–70 | | 3+4/5x=9/10 | | 2x−9=−29 | | 5x÷8=15 | | 13=8x95x8 | | 3|2x−1|=18 | | 2x-5/7=10 | | 50=x/20 | | 1+4x=-5+4x | | 4x+(3x-1)=60 | | 49m=77 |

Equations solver categories